Participation in the Chronic Disease Management Program (Prolanis) and Its Impact on Elderly Quality of Life - Haslina; Asrianto, La Ode; Binawarti, Wa Ode (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2025)
This study originates from the issue of the crucial role of the Chronic Disease Management Program (Prolanis) for the elderly, considering that older adults are vulnerable to health deterioration that affects their quality of life. The program is expected to improve the physical, psychological, and social conditions of the elderly through structured routine activities. The main objective of this research is to analyze the extent to which elderly participation in the Prolanis program contributes positively to a better quality of life. This is important to ensure that community-based health activities are truly effective and relevant to the needs of the elderly. The research employed a quantitative approach with a cross-sectional design. Primary data were obtained through questionnaires distributed to all respondents involved. The sampling technique used was total sampling, meaning that the entire population became part of the study. Data analysis was conducted using univariate methods to describe the distribution of variables and bivariate methods to examine the relationships between the studied variables. The results show that the level of elderly participation in Prolanis activities is relatively good and is directly proportional to the improvement in their perceived quality of life. These findings indicate a significant relationship between elderly involvement in Prolanis and their quality of life, suggesting that this program can be regarded as an effective strategy to improve the well-being of older adults in the community.